Academic Difficulties in Children with Prenatal Alcohol Exposure: Presence, Profile, and Neural Correlates. (24th March 2017) - Glass, Leila; Moore, Eileen M.; Akshoomoff, Natacha; Jones, Kenneth Lyons; Riley, Edward P.; Mattson, Sarah N.
Abstract : Background: Academic achievement was evaluated in children with heavy prenatal alcohol exposure to determine potential strengths and weaknesses, evaluate the utility of different definitions for identifying low academic performance, and explore the neural correlates that may underlie academic performance. Methods: Children (8 to 16 years) were assessed using the WIAT‐II. Patterns of performance were examined in 2 subject groups: children with heavy prenatal alcohol exposure ( n = 67) and controls ( n = 61). A repeated‐measures MANCOVA examining group differences on academic domain (reading, spelling, math) scores was conducted. Post hoc comparisons examined within‐group profiles. Numbers and percentage of children with low achievement were calculated using several criteria. In a subsample ( n = 42), neural correlates were analyzed using FreeSurfer v5.3 to examine relations between cortical structure (thickness and surface area) and performance. Results: The alcohol‐exposed group performed worse than controls on all domains and had a unique academic profile, supported by a significant group × academic domain interaction ( p < 0.001). For the alcohol‐exposed group, math reasoning was significantly lower than numerical operations, which was significantly lower than spelling and word reading. Over half of the alcohol‐exposed group (58.2%) demonstrated low achievement on 1 or more academic domains. The number and percentage of children meeting criteria for low achievement varied based on the domain and definition used. The imaging analysis identified several surface area clusters that were differentially related to math (L superior parietal and R lateral/middle occipital) and spelling (bilateral inferior and medial temporal) performance by group, with no relations for the other academic domains. Generally, scores improved as surface area decreased in controls, whereas no relation or a positive relation was observed in the alcohol‐exposed group. Conclusions: Alcohol‐exposed children demonstrated deficits in academic performance across domains and definitions, with a relative weakness in math functioning. Atypical brain development may contribute to these impairments in academic achievement. Understanding academic difficulties can assist in advocating effectively for alcohol‐exposed children. Abstract : Children with heavy prenatal alcohol exposure were compared to non‐exposed peers on measures of academic achievement. Alcohol‐exposed children performed significantly worse on all academic domains, though showed particular weakness in math performance. Academic difficulties may be related to atypical brain development, as spelling and math performance were negatively associated with clusters of cortical surface area for non‐exposed children but not alcohol‐exposed children. Greater understanding of academic performance in this population can assist in advocating effectively for alcohol‐exposed children.